Sub-Saharan Migrants in Morocco in an Era of Pandemics - Lahrech, Wafae (HAPSc Policy Briefs Series, 2022)
This study focuses on the socio-economic issues of the COVID-19 pandemic on the situation of sub-Saharan migrants (in great vulnerability) in Morocco. It also examines the effectiveness of the humanitarian responses of national and international institutions to the needs felt and expressed by migrants, and particularly sub-Saharan migrants. Migration dynamics are being challenged by the unprecedented - beyond borders - extension of the pandemic that are difficult to measure or prevent. This conditions the situation of sub-Saharans in Morocco between returning to their countries and experiencing an uncertain future in the country of stay.